Peran Green Marketing Memoderasi Pengaruh Inovasi Produk, Persepsi Harga dan Kesadaran Lingkungan terhadap Keputusan Pembelian Beras Organik di Kabupaten Bandung - Elwisam; Murni Sophianur Batubara (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Research was conducted to analyze the influence of product innovation, price perception and environmental awareness on purchasing decisions moderated by green marketing. Sampling was based on a purposive sampling technique of 120 respondents with the criteria being consumers who had previously purchased organic rice and consumers who had repurchased organic rice. The data in this study used Structural Equation Modeling (SEM)-PLS with WarpPLS 7.0. The research results concluded that: Product innovation and environmental awareness have a positive and significant effect on purchasing decisions; price perception and green marketing have no influence on purchasing decisions; green marketing significantly positively moderates the influence of product innovation on purchasing decisions; Green marketing significantly negatively moderates price perception and environmental awareness on purchasing decisions. The managerial implications that can be given are proving that the products produced are safe for consumption by guaranteeing certified products, increasing promotions and guaranteeing that the products produced are environmentally friendly.